Strategi Menumbuhkan Kreativitas dan Keterampilan Kewirausahaan Anak melalui Kegiatan Bermain di Sekolah Dasar - Arvita, Tihan; Zahara, Dini Putri; Hia, Alice Felicia Azaria; Pateka, Philsa Arin; Sholeh, Muhammad (Asian Journal of Early Childhood and Elementary Education, 2024)
Creativity and entrepreneurial skills are important aspects in developing individuals who are able to face future challenges resiliently. This research aims to identify and analyze effective strategies in fostering children's creativity and entrepreneurial skills through play activities in elementary schools. This study uses a qualitative method, where the approach is through a systematic literature review (SLR) to explore the best way to understand the essence of entrepreneurship education for prospective teachers and observe the implementation of this strategy in several elementary schools. The SLR method is used to identify, review, evaluate, and interpret all available research on a topic area of interest, with specific relevant research questions. The findings show that a structured and directed play approach can be an effective means of developing children's creativity and entrepreneurial skills. The implications of this research provide a better understanding of the importance of integrating play activities in the elementary school curriculum to strengthen aspects of creativity and entrepreneurship in children.